Mortal heart - LaFevers, Robin (LaFevers, Robin. His fair assassin, 2014)
Annith's worst fears are realized when she discovers that, despite her lifelong training to be an assassin, she is being groomed by the abbess as a Seeress, to be forever shut up in the convent of Saint Mortain.